(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
The writing of this article is motivated by the author’s interest in the role of Battalion 328 in suppressing the DI/TII rebellion in Banten. The involvement of the 328 Infantry Battalion cannot be separated from Indonesia’s post-independence history. This special force formed by the TNI had an important role in maintaining political stability and security in West Java, especially Banten. Because there has not been much research on the 328 Infantry Battalion, this research will reconstruct the role of the 328 Infantry Battalion in suppressing DI/TII in Banten. The research method used in writing this article is the historical method, with research stages consisting of heuristics, criticism, interpretation, and historiography. Through this research can be known: 1) the background of the formation of Infantry Battalion 328; and 2) The strategies of the 328th Infantry Battalion in suppressing the DI/TII rebellion in Banten.